Usefulness of dynamic contrast-enhanced MR imaging in the evaluation of pulmonary isolated lesions - Li, Zhiyong; Zhang, Tingting; Wu, Jianlin; Liu, Wei; Wei, Qiang; Xu, Bin; Han, Rui (The Chinese-German journal of clinical oncology, 2010)
Objective： The aim of our study was to investigate the value of dynamic contrast-enhanced MRI for evaluating differential diagnosis of pulmonary isolated lesions. Methods： Twenty-nine consecutive patients enrolled in this study, all of whom underwent DCE-MRI examinations and received a histologic and clinical diagnosis. Among these, lung tuberculoma 7 cases, harmatoma 3 cases, peripheral lung cancer 19 cases. DCE-MRI was acquired with 3D LAVA technique, total 18 phases were acquired, scanner time of per phase was 5-7″. After contrasting agent, twice successive scanning was acquired at 10″ and 50″. Then 1′30″, 2′, 2′30″, 3′, 3′30″, 4′, 5′, 6′, 7′, 8′, 9′, 10′, 11′, 12′ performed scanning. Region of interest was placed on the Maximum level in the tumors. According to Schaefer＇s standard, four types of time signal intensity curve （TIC） were classified, which were A, B, C and D. Compared the dynamic parameters between benign and malignant nodules. Results： Lung tuberculoma may display three curves： A type 1 case, ring-shaped enhancement 4 cases （periphery ring A type, central region D type）, D type 2 cases. Harmatoma may display three curves： A type 1 case, C type 2 case. Peripheral lung cancer may display A type. Except 2 cases D type lung tuberculoma, we compared curve data of 8 cases benign nodules （including tuberculoma Atype and periphery ring Atype, harmatoma Atype and C type） and lung cancer. SlEP%： benign nodules 0.7885 ±0.5543, lung cancer 1.2623 ±0.3059, P 〈 0.05; MER： benign nodules 1.0007 ± 0.4251, lung cancer 1.3694 ±0.2740, P 〈 0.05; washout： P 〉 0.05. Conclusion： Lung MR imaging is helpful to diagnosis and differential diagnosis of isolated benign and malignant nodules. SIEP% and MER could offer valuable information. The evolution of global tuberculosis may be from A type to ring-shaped ennoblement to D type. It was easy to do right diagnosis to lung tuberculoma with ring-shaped ennoblement and D type. Peripheral lung cancer commonly displayed A type and needed identification with acute inflammation. So, it is important to anti-inflammatory follow-up for a few A type nodules.